The Nationalism Cultivation Through the Folk Songs In Sandhy Putra Kindergarden Surakarta - Widjanarko, Paulus (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to introduce the folk songs, because the folk songsloaded with positive values and moral message such as nationalism, that can be abasic character formation. This research used qualitative descriptive method,which means that the discussed problems in this research illustrate or elaborate onthe state or phenomenon. The results of this research was given materials aboutfolk songs by story telling model or fairy tales. The teacher taught the gamesong such as âThe Padhang Bulanâ which tells story of love to God and theuniverse and its contents as God creation. This song also told us about the carenature and togetherness towards fellow human beings and grateful feeling. Inaddition to folk songs learning achievement by story telling, teachers usedthe audio visual media on the folk songs showed about Indonesias natural beautyand cultural richness of Indonesia.Keywords: character cultivation, folk songs.